MODELING OF M2M TRAFFIC OF MODERN COMMUNICATION NETWORKS - Chumachenko, Sergii; Chumachenko, Bohdan; Maloied, Maryna; Odarchenko , Roman; Paziuk, Andrii (Science-based technologies, 2024)
The development of communication networks leads to the expansion of their capabilities in traffic transmission. In connection with the increase in the volume of processed and transferred data, in particular the traffic of transferring media files, data processing specialists strive to improve the quality of images by constantly improving the means and standards of multimedia presentation. It is important to note that user-generated media traffic is characterized by stability and predictability, as the data is transferred primarily in response to user requests. However, in addition to media traffic, today's networks face an increasing flow of data between devices, mostly within the concept of the Internet of Things. The peculiarity of M2M traffic is that it is generated by a significant number of devices, which can potentially be much larger than the number of ordinary users. This type of traffic differs from other priority aspects because the devices that generate it work on the basis of stable algorithms and do not pay much attention to other factors. This can increase network load and create additional vulnerabilities. In the context of this research, considerable attention is paid to the development of new technologies for efficient M2M traffic management. For example, LTE and 5G mobile network standards include mechanisms for servicing and managing M2M traffic. The paper presents the results of M2M traffic analysis using the model proposed by 3GPP, which has been thoroughly analyzed and refined to improve its simulation. Analytical descriptions of the model and results of simulation modeling allow understanding the impact of M2M traffic on the quality of service in communication networks. The obtained results can be used both for modeling the traffic of M2M devices and for determining their parameters. For example, they can be used to develop algorithms for controlling such devices during network overloads.